IJCM_373A: Effectiveness of a workshop on Making effective presentation in scientific conferences in improving the knowledge and perception of faculty members of various health science courses in Mangalore, India. - Joseph Nitin; Karnad Shreekanth. D. (Wolters Kluwer Medknow Publications, 2024)
Background: Presentation at scientific conferences requires skills that may not be familiar among faculty members. Objective: To assess the knowledge and perceptions of faculty members before and after attending a workshop on making effective presentations at scientific conferences. Methodology: This was an intervention study among 31 faculty members who attended a workshop in April 2023. Data were collected using a Microsoft form. Results: Results: Eighteen (58.1%) carried first aid kits while travelling for conferences. Majority of the participants felt that the interaction with the audience was better in onsite conferences than in online conferences. Majority of them preferred oral presentations to reach a wider audience. Less than 10% of the participants indulged in post-conference activities. Self-perceived confidence level in attending conferences and self-perceived knowledge regarding activities to be performed before, during, and after attending conferences were reported to significantly improve (p<0.001) after attending the workshop by the participants. The median knowledge score of the participants in the pre-test was 12, IQR (11, 16), and in the post-test was 15, IQR (14, 18) (Z=3.422, p=0.001). Conclusion: The workshop was found to increase the participants' knowledge and confidence level in essential aspects of conference presentations. Hence more such training programs are required among health care professionals.